281 RELATIONSHIP OF GENDER TO CORONARY PLAQUE TYPE AND DISTRIBUTION: ANALYSIS BY 64-DETECTOR COMPUTED TOMOGRAPHIC ANGIOGRAPHY. Issue 1 (1st January 2007) - Lubarsky, L.; Prakash, M.; Gottsegen, J.; Coplan, N.; Hecht, H.
Abstract : Background: In asymptomatic patients, calcified coronary plaque is greater in men than women at comparable ages. There are no data regarding gender differences in the composition and distribution of coronary plaque, including noncalcified and calcified components, in patients with established CAD. Methods: Fifty patients (29 male, 21 female) with established CAD undergoing 64-detector computed tomographic angiography (CTA) and calcium score were evaluated with the AHA 18-segment model. In each segment, plaque type was characterized as totally noncalcified (TNC), predominantly noncalcified (PNC), predominantly calcified (PC), or totally calcified (TC). Results: There was no statisticaly significant difference in plaque type or calcium score between men and women (see Table ). Totally or predominantly noncalcified plaques were more common than totally or predominantly calcified plaques in the RCA (69%), LCX (65%), and LAD (55%) and in the proximal (54%), mid- (65%), and distal (77%) vessel. Conclusion: (1) In patients with established CAD, coronary artery plaque types were similarly distributed in men and women. (2) TNC plaque was significantly more common ( p < .01) than the other plaque types.